Pengembangan PBL dan PJBL Terintegrasi PSE Mindfulness: Peningkatan Kompetensi Guru SD Gugus Imam Bonjol dalam Implementasi Kurikulum Merdeka: The Development of PBL and PJBL Integrated PSE Mindfulness: Improving Elementary School Teachers’s Competencies in The Implementation of Merdeka Curriculum - Mulyani, Petra Kristi; Trimurtini, Trimurtini (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The implementation of Kurikulum Merdeka (KM) at Imam Bonjol Elementary School Cluster, Salatiga, requires teachers with supporting competencies. The aim of this community service activity is to integrate Problem Based Learning (PBL) and Project Based Learning (PJBL) with Social Emotional Learning (PSE) so that it can improve teacher's competencies. The team provided community service activities included training, strengthening, and mentoring to develop PBL and PJBL learning integrated with PSE mindfulness in the implementation of KM. The community service activities used PALS (Participatory Action and Learning System) method. Partner teachers participated in socialization, training, assistance in development, and institutionalization on PBL and PJBL integration with PSE mindfulness. The results showed that 100% of teachers agreed that mindfulness was important to be applied in classroom learning and 83.33% of teachers agreed that mindfulness could be applied individually by teachers or students. The teachers' understanding on the meaning of mindfulness reached 100%. Meanwhile, the teachers' understanding on examples of mindfulness practices both individually and integrated into learning, especially in PBL and PJBL learning, reached 75%. The influence of mindfulness practices related to teacher duties was 89.49%, meaning that it was influential significantly. So that this mindfulness practice can have a positive effect on teachers both in their personal lives and in their duties as teachers.